The Constitution of the Republic of Serbia and rationalized decentralization - Čiplić, Svetozar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The Work consists of several parts. The first part is a brief overview of the problems that have emerged in Serbia due to the vertical organization of government.The Second part relates to the current constitutional arrangements, while the third part deuoped to examples of certain European countries (Finland and Italy), where decentralization og protecting national minorities and ethnic communities. The next section refers to the theoretical concerns about decentralization, and the classification of rregionalism. The last part is an attempt to determine a larger number of elements rationalized decentralization.